2009
DOI: 10.1002/jcla.20280
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐C1q antibodies: association with nephritis and disease activity in systemic lupus erythematosus

Abstract: Background: Anti‐C1q antibodies have been described in systemic lupus erythematosus (SLE) as well as in other connective tissue diseases. They have been considered as a marker for disease activity and presence of nephritis.Objective: The aim of this study was to determine the prevalence of anti‐C1q antibodies in Brazilian lupus patients as well as analyze their association with different clinical and serologic parameters.Methods: Sera from 81 SLE patients, based on the American College of Rheumatology (ACR) cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…It was reported that IgG2 subclass of anti-C1q antibodies might be pathogenic and IgG3 subclass of anti-C1q might be more specific bio-marker for monitoring disease activity [21]. Maura et al had reported a positive correlation between high titres of anti-C1q antibodies, and SLEDAI scores in Brazilian SLE patients and had shown an association of anti-C1q antibodies with LN [22]. Our study also supported this finding.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that IgG2 subclass of anti-C1q antibodies might be pathogenic and IgG3 subclass of anti-C1q might be more specific bio-marker for monitoring disease activity [21]. Maura et al had reported a positive correlation between high titres of anti-C1q antibodies, and SLEDAI scores in Brazilian SLE patients and had shown an association of anti-C1q antibodies with LN [22]. Our study also supported this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Rosen and co-workers suggested that a considerable number of lupus autoantigens were clustered within apoptotic blebs [49,50]. This condition is further compounded by the presence of anti-C1q autoantibodies detected in the sera of a number of patients suffering from SLE [51][52][53][54][55]. The CRT binds to the CD91 and C1q, which is known to bind to the CRT through its collagenous "tail", forms a complex with CRT/CD91.…”
Section: Clearance Of Apoptotic and Necrotic Cells Via C1qmentioning
confidence: 99%
“…Our study primarily focused on the analysis of autoantibodies against intact C1q since these autoantibodies have been best described to correlate with SLE disease activity [34,35]. In addition, using intact C1q maybe best reflects the situation occurring in vivo, allowed the analysis of high-affinity antibodies, and avoided manipulations of the molecule as well as the presence of non-physiological components such as peptide 2J [29] and neutravidine [36].…”
Section: Discussionmentioning
confidence: 99%